Electropneumotactile Stimulation: Multimodal Haptic Actuators Enabled by a Stretchable Conductive Polymer on Inflatable Pockets. Issue 6 (5th May 2020) - Carpenter, Cody W.; Malinao, Marigold G.; Rafeedi, Tarek A.; Rodriquez, Daniel; Tan, Siew Ting Melissa; Root, Nicholas B.; Skelil, Kyle; Ramírez, Julian; Polat, Beril; Root, Samuel E.; Ramachandran, Vilayanur S.; Lipomi, Darren J.
Abstract: A type of haptic device is described that delivers two modes of stimulation simultaneously and at the same location on the skin. The two modes of stimulation are mechanical (delivered pneumatically by inflatable air pockets embedded within a silicone elastomer) and electrical (delivered by a conductive polymer). The key enabling aspect of this work is the use of a highly plasticized conductive polymer based on poly(3, 4‐ethylenedioxythiphene) (PEDOT) blended with elastomeric polyurethane (PU). To fabricate the "electropneumotactile" device, the polymeric electrodes are overlaid directly on top of the elastomeric pneumatic actuator pockets. Co‐placement of the pneumatic actuators and the electrotactile electrodes is enabled by the stretchability of the PEDOT:tosylate/PU blend, allowing the electrotactiles to conform to underlying pneumatic pockets under deformation. The blend of PEDOT and PU has a Young's modulus of ≈150 MPa with little degradation in conductivity following repeated inflation of the air pockets. The ability to perceive simultaneous delivery of two sensations to the same location on the skin is supported by experiments using human subjects. These results show that participants can successfully detect the location of pneumatic stimulation and whether electrotactile stimulation is delivered (yes/no) at a rate significantly above chance (mean accuracy = 94%). Abstract : A device that can deliver sensations to the skin (a "haptic" device) using two modalities simultaneously is described: a pneumatic modality and an electrical one. The enabling feature of the device is the use of a stretchable conductive polymer bonded to inflatable pockets. Human participants are able to discern the two modalities when used simultaneously.